Neutral pion production at midrapidity in pp and Pb-Pb collisions at √sNN=2.76TeV - Abelev, Betty; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Fasel, Markus; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (The European physical journal. C, Particles and fields, 2014)
Invariant yields of neutral pions at midrapidity in the transverse momentum range 0.6<pT<12GeV/c measured in Pb-Pb collisions at √sNN=2.76TeV are presented for six centrality classes. The pp reference spectrum was measured in the range 0.4<pT<10GeV/c at the same center-of-mass energy. The nuclear modification factor, RAA, shows a suppression of neutral pions in central Pb-Pb collisions by a factor of up to about 5≲pT≲7GeV/c. The presented measurements are compared with results at lower center-of-mass energies and with theoretical calculations.
The ALICE Collaboration: B. Abelev, V. Anguelov, F. Bock, O. Busch, M. Fasel, P. Glässel, J. Klein, L. Leardini, X.-G. Lu, A. Maire, J. Mercado Perez, H. Oeschler, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, S. Vallero, M.A. Völkl, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann und weitere 912
Gesehen am 06.07.2020
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt